2016
DOI: 10.1016/j.bj.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Profile of glycated-hemoglobin, antioxidant vitamin and cytokine levels in pulmonary tuberculosis patients: A cross sectional study at Pulmonary Diseases Center Semarang City, Indonesia

Abstract: BackgroundUncontrolled blood glucose, which marked by high level of HbA1c, increases risk of pulmonary TB because of cellular immunity dysfunction. This study aimed to analyze profile of glycated hemoglobin, antioxidant vitamins status and cytokines levels in active pulmonary TB patients.MethodsThis was a cross sectional study, conducted at Pulmonary Diseases Center Semarang City, Indonesia. Study subject consisted of 62 pulmonary TB patients, diagnosed with positive acid fast bacilli and chest X-ray. ELISA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Reasons may be as follows. Both DM and TB are associated with malnutrition and this association may be stronger with a longer duration of DM and multiple episodes of TB [ 32 ]. Amongst our study group, the proportion with older age and retreatment TB at nearly 30% was higher than found in a previous study of TB patients [ 14 ], a finding similar to that observed in Guangzhou [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reasons may be as follows. Both DM and TB are associated with malnutrition and this association may be stronger with a longer duration of DM and multiple episodes of TB [ 32 ]. Amongst our study group, the proportion with older age and retreatment TB at nearly 30% was higher than found in a previous study of TB patients [ 14 ], a finding similar to that observed in Guangzhou [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted in Indonesia, cytokines in blood were determined in two defined groups of patients depending on their 1AC levels (<7 and >7%). Patients with 1AC >7% had the same levels of IFN-γ and IL-12 than the patients with 1AC <7%, but had lower levels of vitamin A (Ginandjar et al, 2016). Deficiency in vitamin A levels has been recently associated to a higher risk of TB in Moroccan patients (Qrafli et al, 2017), and this vitamin was found in lower levels in TB patients than in healthy controls (Oh et al, 2017).…”
Section: Clinical Features Of T2d and Their Effects On Response To Mmentioning
confidence: 99%
“…Kawasan Asia menyumbangkan sebanyak 20% kematian yag disebabkan oleh tuberkulosis terutama pada negara berkembang seperti India, Indonesia, dan Cina (World Health Organization, 2016). Tingginya angka kejadian tuberkulosis yang menyebabkan kualitas hidup menurun serta dampak yang ditimbulkan sampai dengan kematian yang terjadi, menyebabkan tuberkulosis menjadi masalah kesehatan yang harus dihentikan terutama pada negara berkembang seperti Indonesia (Ginandjar et al, 2016) Banyak faktor yang menyebabkan tingginya kejadian tuberkulosis yaitu faktor eksternal dan faktor internal. Faktor eksternal yang mempengaruhi seperti jarak pelayanan kesehatan serta lingkungan yang mendukung pengobatan pada penderita tuberkulosis.…”
Section: Latar Belakangunclassified